Energy analysis of the convective drying of iron ore fines - e Souza Amarílis Severino; de Souza Pinto Thiago César de; Sarkis Alfredo Moisés; de Pádua Thiago Faggion; Béttega Rodrigo (Chemical Industry and Chemical Engineering Quarterly, 2023)
Drying operations in iron ore processing plants have a particularly high energy demand due to the massive solid flow rates employed in this industry. A 33 full-factorial design was applied to investigate the effects of air temperature, airflow velocity, and solids load on the drying time and the specific energy consumption (SEC) of the convective drying of iron ore fines in a fixed bed. The results demonstrated that each drying air condition was associated with an optimal solids load that minimized the SEC. A load of 73 g (bed height of about 0.8 cm) was identified and validated as the optimal condition in terms of energy consumption for the configuration with the highest air temperature (90°C) and airflow velocity (4.5 m/s). This condition resulted in a drying time of 29.0 s and a corresponding SEC of 12.8 MJ/kg to reduce the moisture from 0.11 kg water/kg dry solids to a target of 0.05 kg water/kg dry solids. Identifying the optimum values for the process variables should assist in designing and operating energy-efficient convective dryers for iron ore fines.